Analysis of Community Roles in Empowering Marginalized Children (Case Study: Save Street Child Surabaya Community) - Ahmad Bagus Rohim; Lukman Arif (Publik : (Jurnal Ilmu Administrasi), 2026)
Surabaya is a big city in Indonesia with high economic growth. But besides that, there are still many people in Surabaya who are still in the underprivileged category. Many of them are married but do not meet their daily needs. Therefore, children from underprivileged families help earn additional income. These children work on the streets and spend almost all their days on the streets. Because of that, they are vulnerable to being marginalized by others, which can cause children to become demotivated. Therefore, a community emerged that protects and empowers them, namely the Save Street Child Surabaya Community. With programs that are run consistently with high commitment, it is hoped that marginal children who are fostered will become better and get out of their current conditions. The purpose of this study is to analyze the role that has been carried out by the Save Street Child Surabaya Community in empowering marginal children, according to Jim Ife and Frank Tesoriero, which consists of facilitating, educating, representing, and technical roles, each of which has other sub-roles. This study uses qualitative research with a case study approach, with a technique for determining informants through Purposive Sampling. This study also uses data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the Save Street Child Community in Surabaya carries out its role in empowerment well, but there is still one sub-role that is not carried out due to a lack of manpower